Marketing Humanity - How Inclusive Employment Shapes Brand Equity in Social Cafes – A Case Study of Kopi Kamu Wijaya, Jakarta - Annisa Al-Rabbani; Andi Azhar (Jurnal Manajerial, 2026)
Background - Humanistic marketing (SD Logic & Signal Theory) is limited to Western contexts. An Indonesian F&B SME (Kopi Kamu Wijaya), which employs Down Syndrome servers, is testing inclusion as a competitive asset. Objective - Developing a three-layer Layered Humanistic Marketing model towards collectivist loyalty of Southeast Asian MSMEs. Design/Methodology/Approach - Constructivist qualitative research through a single case study of Kopi Kamu Wijaya. Purposive and snowball sampling involved 6 informants (1 operational manager, 1 employee with Down Syndrome, 1 regular employee, 2 customers, 1 coffee industry expert). Data triangulation from semi-structured interviews (15-20 minutes), non-participant observation during peak/low hours, and marketing document analysis. 6-phase thematic processing using Atlas.ti with Guba & Lincoln credibility criteria. Results and Discussion - Three-layer model: (1) Moral leadership, (2) Inclusive workforce (dignity of work), (3) Consumer resonance (empathy→WOM→loyalty). Inclusion as strategic differentiation. Conclusion - "Rain of moral values" leadership→consumers create sustainable brand equity. Research Implications - Theoretical: expanding non-Western SD Logic. Practical: SME blueprint. Policy: industry mentoring. Research Limitations - Single case, no quantitative metrics. Needs multi-case validation.